Learner Open Modeling in Adaptive Mobile Learning System for Supporting Student to Learn English - Nguyen, Viet Anh; Pham, Van Cong (International Journal of Interactive Mobile Technologies (iJIM), 2011)
This paper represents a personalized context-aware mobile learning architecture for supporting student to learn English as foreign language in order to prepare for TOEFL test. We consider how to apply open learner modeling techniques to adapt contents for different learners based on context, which includes location, amount of time to learn, the manner as well as learner’s knowledge in learning progress. Through negotiation with system, the editable learner model will be updated to support adaptive engine to select adaptive contents meeting learner’s demands. Empirical testing results for students who used application prototype indicate that interaction user modeling is helpful in supporting learner to learn adaptive materials.